National and Ethnic Identity in the Constitutions of the BRICS Countries - E. Gladun (BRICS Law Journal)
The article presents the transformation of the concept of ethnicity, which is evident in many countries across the world in the context of changing world order. The author demonstrates the tendency to accept poly ethnicity and multiple faces in modern states, including the BRICS countries. Also, the author examines various approaches to defining ethnicity that exist both in legal science and in other social sciences. Using the example of the BRICS countries, it is shown that the legal recognition of ethnic identity, language and cultural differences occurs at the level of national constitutions since these categories are essential for recognition and awareness of each citizen and each national society in existing multinational states. The author proves that the formation of constitutional and legal norms taking into account the essence of ethnicity will contribute to the sustainable development of multinational states.